(untitled) (Research, Society and Development, 2020)
Currently, the success of nanotechnology affects several areas of science, medicine, technology and, especially, the food industry. Silver nanoparticles (Ag-NPs) stand out, with their antimicrobial effect. Salmonella is a cause of foodborne diseases and there are reports of resistant serotypes. The use of Ag-NPs is an alternative for bacterial control in foods. The aim of this study was synthesize, characterize and verify the antimicrobial activity of Ag-NPs on serotypes of Salmonella. The size of Ag-NPs was estimated and it was possible to detect two populations of 4.7 ± 0.09 and 35.7 ± 2.12. The zeta potential was -33.7 ± 11.8 mV indicating good dispersion stability.Ag-NP antimicrobial activity was determined from minimum inhibitory concentration (MIC).The lowest MIC found was 4.7 μg·mL-1 for Salmonella Enteritidis and the highest was 27.7 μg·mL-1 for Salmonella Infantis 1 isolate.The use of Ag-NPs is promising with respect to antimicrobial activity, however, improvements in synthesis methods should be explored in order to make commercial use viable.